Spillover effects of the US economic policy uncertainty in Latin America - Coronado, Semei; Martínez, José N.; Venegas-Martínez, Francisco (Estudios de Economía, 2020)
This paper is aimed at assessing the spillover effects of the US Economic Policy Uncertainty (EPU) in macroeconomic variables of major Latin American Countries (LAC): Mexico, Colombia, Brazil, and Chile. To do that, we estimate a set of two-country Structural Vector Autoregressive (SVAR) models for 1997-2019; each model includes the US and one of the LAC. We use the following variables: EPU indexes, exchange rates, consumer price indexes, industrial production (IP), and interest rates (IR) of the US and the studied LAC. The main finding is that positive shocks in the US EPU index lead to currency depreciation for all four LAC; the largest effect is for Mexico. Other statistically significant results are a brief and small positive impact on Colombia’s IP and a positive impact on Mexico’s IR. The remaining LAC’s estimates are statistically insignificant. For this reason, we applied Rossi and Wang’s (2019) robust Granger causality tests that considers structural breaks. Finally, the estimates before and after the 2008 financial crisis suggest that LAC became slightly more responsive to US EPU shocks after the crisis.